2002
DOI: 10.1089/104303402760128568
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Chimeric Adenovirus Vector Enhances BMP2 Production and Bone Formation

Abstract: Recombinant adenoviral vectors have potential for the treatment of a variety of musculoskeletal defects and such gene therapy systems have been a recent research focus in orthopedic surgery. In studies reported here, two different adenovirus vectors have been compared for their ability to transduce human bone marrow mesenchymal stem cells (hBM-MSCs) and elicit bone formation in vivo. Vectors consisted either of standard adenovirus type 5 (Ad5) vector or a chimeric adenovirus type 5 vector that contains an aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 32 publications
6
101
0
Order By: Relevance
“…Perhaps the reduced number of cells expressing PS in the mouse compared to human nerve arises because of the nature of the mouse model. Previous studies have shown that the BMP2-producing cells are rapidly cleared from the tissues approximately 5 days after their injection [11, 24, 25]. Thus, the less robust response in mice may reflect the low-level short-term expression of BMP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the reduced number of cells expressing PS in the mouse compared to human nerve arises because of the nature of the mouse model. Previous studies have shown that the BMP2-producing cells are rapidly cleared from the tissues approximately 5 days after their injection [11, 24, 25]. Thus, the less robust response in mice may reflect the low-level short-term expression of BMP2.…”
Section: Discussionmentioning
confidence: 99%
“…022137) transgenic mouse [17] was purchased from Jackson Laboratories and crossed with the R26R td Tomato red mouse to generate the mouse termed Wnt1 Cre2 :Ai9Tm. Heterotopic bone formation was established in the mice through an intramuscular injection into the quadriceps of C57BL/6 mouse fibroblasts (1 x 10 5 , 5 x 10 5 , 1 x 10 6 , or 5 x 10 6 in 300 μL of phosphate-buffered saline) transduced with an E1–E3 deleted adenovirus expressing BMP2 [11]. …”
Section: Methodsmentioning
confidence: 99%
“…BM-MSCs were derived from discarded human bone marrow from healthy donors as previously described. 11,12 Cells were isolated by gradient density centrifugation on Ficoll-Paquet PLUS (Amersham Pharmacia Biotech, Piscataway, NJ, USA), plated at 5 Â 10 6 cells/cm 2 in the medium above, and enzymatically collected before becoming confluent. 13 …”
Section: Cellsmentioning
confidence: 99%
“…Recently, we have described, a novel recombinant chimeric adenoviral BMP2 vector, 11,12 which consists of Ad5 containing a fiber gene of adenovirus type 35 (Ad5F35-BMP2). Comparison of Ad5F35-BMP2 with Ad5-BMP2 demonstrated the ability of the former to elicit significantly higher expression of BMP2 in vitro in human bone marrow MSCs (BM-MSCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation